Alzheimer’s Disease: In Vitro and In Vivo Evidence of Activation of the Plasma Bradykinin-Forming Cascade and Implications for Therapy - Allen P. Kaplan; Berhane Ghebrehiwet; Kusumam Joseph (Cells)
The plaques associated with Alzheimer’s disease are formed as a result of the aggregation of Aβ peptides, which vary in length from 38 to 43 amino acids. The 1-40 peptide is the most abundant, while the 1-42 peptide appears to be the most destructive to neurons and/or glial cells in a variety of assays. We have demonstrated that aggregated Aβ, a state prior to plaque formation, will activate the plasma bradykinin-forming pathway when tested in vitro. Aggregation is zinc-dependent, optimal at 25–50 µM, and the rate of aggregation is paralleled by the rate of activation of the bradykinin-forming pathway as assessed by plasma kallikrein formation. The aggregation of Aβ 1-38, 1-40, and 1-42 is optimal after incubation for 3 days, 3 h, and under 1 min, respectively. The cascade is initiated by the autoactivation of factor XII upon binding to aggregated Aβ; then, prekallikrein is converted to kallikrein, which cleaves high-molecular-weight kininogen (HK) to release bradykinin. Studies by a variety of other researchers have demonstrated the presence of each “activation-step” in either the plasma or spinal fluid of patients with Alzheimer’s disease, including activated factor XII, kallikrein, and bradykinin itself. There is also evidence that activation is more prominent as dementia worsens. We now have medications that can block each step of the bradykinin-forming pathway as currently employed for the therapy of hereditary angioedema. Given the current state of therapy for Alzheimer’s disease, which includes monoclonal antibodies that retard the rate of progression by 30% at most and have significant side effects, it seems imperative to explore prophylaxis using one of the long-acting agents that target plasma kallikrein or factor XIIa. There is a long-acting bradykinin antagonist in development, and techniques to target kallikrein mRNA to lower levels or knock out the prekallikrein gene are being developed.